2015
DOI: 10.1177/0962280215570722
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of causal effects of binary treatments in unconfounded studies with one continuous covariate

Abstract: The estimation of causal effects in nonrandomized studies should comprise two distinct phases: design, with no outcome data available; and analysis of the outcome data according to a specified protocol. Here, we review and compare point and interval estimates of common statistical procedures for estimating causal effects (i.e. matching, subclassification, weighting, and model-based adjustment) with a scalar continuous covariate and a scalar continuous outcome. We show, using an extensive simulation, that some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 68 publications
0
29
0
Order By: Relevance
“…The probability to reach the threshold or above (defined as a propensity score) was determined by multivariate binary logistic regression using the aforementioned 23 baseline covariates. After estimating the propensity score, the participants whose propensity scores were non-overlapped between the higher and the lower groups of the test threshold, that is, outside the common support, were trimmed out and the remaining subsample was used for a propensity score analysis [13].…”
Section: A Propensity Score Analysismentioning
confidence: 99%
“…The probability to reach the threshold or above (defined as a propensity score) was determined by multivariate binary logistic regression using the aforementioned 23 baseline covariates. After estimating the propensity score, the participants whose propensity scores were non-overlapped between the higher and the lower groups of the test threshold, that is, outside the common support, were trimmed out and the remaining subsample was used for a propensity score analysis [13].…”
Section: A Propensity Score Analysismentioning
confidence: 99%
“…The statistical literature includes many procedures for estimating treatment effects in observational studies. Gutman and Rubin showed that when Y and X are scalar and continuous, and treatment assignment only depends on X , only a few of the common procedures are generally statistically valid, with the most promising ones being matching with replacement for effect estimation, with or without covariance adjustment, combined with within‐treatment group matching for sampling variance estimation, suggested by Abadie and Imbens , and called in Gutman and Rubin M–N–m and M–C–m (M, cross‐group matching for point estimate; C/N, with/without covariance adjustment; m, matching within treatment group for sampling variance estimate).…”
Section: Introductionmentioning
confidence: 99%
“…We compare the validity and performance of MITSS to the most promising methods identified by Gutman and Rubin using Neyman's framework of frequentist operating characteristics, in which an α ‐level interval estimate is ‘valid’ if, under repeated sampling from the population (finite or super), it covers the estimand in at least α percent of the samples. In addition to validity, we compare the accuracy, biases, and mean square errors (MSEs) of point estimates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations